Evaluation of microbial quality and the histamine content of dried local herring (Tabagak) produced in Roxas City, Capiz. - Rosellas, Kayra Ninya L. (2023.)
Dried fish is an important food commodity in the Philippines since it is an inexpensive source of high-quality protein. Traditionally, sun-drying of fish often involves unhygienic manufacturing and distribution conditions. Hence this study focused on the assessment of the physicochemical parameters, microbiological quality, and histamine content of the dried local herring (tabagak) from three producers in Roxas City, Capiz. The dried fish samples had pH values ranged from 5.670 - 5.795 and water activity that ranged from 0.741 - 0.763 which were all within the limits of the Philippine National Standards (PNS) for dried fish. The moisture content values ranged from 32.65 - 42.98%, which exceeded the recommended value. The total plate count (TPC) ranged from 1.4x107 - 5.9x107 CFU/g while the yeast and molds count (YMC) ranged from 6.7x105 - 2.1x106 CFU/g. The mean S. aureus count ranged from 1.3x107 - 4.4x107 CFU/g while presence of E.coli count was not detected in all samples. All TPC, YMC, S. aureus, and coliform counts are inferred to go beyond the acceptable limits by the PNS. The histamine varied between 34.63 - 707.03 mg/kg, where samples from producer C had the highest value. Only producer C exceeded the PNS limits for histamine content at 200 mg/kg. These data suggest that dried fish from selected sources in Roxas City may become vessels of foodborne illness if not properly prepared before being consumed. Observance of proper food handling practices will ensure dried fish products are of improved quality and safety. This study could provide information which could encourage active participation of producers and food regulatory agencies alike in practicing food safety.
Thesis (Undergraduate, Bachelor of Science in Food Technology) School of Technology, University of the Philippines Visayas, Miagao, Iloilo. 2023.
Keywords: Dried Local Herring -- Roxas City; Tabagak